2003
DOI: 10.1029/2002ja009469
|View full text |Cite
|
Sign up to set email alerts
|

Reply to comment on “Detection of small comets with a ground‐based telescope” by L. A. Frank and J. B. Sigwarth

Abstract: Citation: Frank, L. A., and J. B. Sigwarth, Reply to comment on ''Detection of small comets with a ground-based telescope'' by L. A. Frank and J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…Hunana et al [23] have presented a detailed review of CGL fluid description in collisionless plasmas and shown the importance of heatflux vectors in astrophysical plasmas. Wang and Hau [24] found that in a homogeneous anisotropic plasma, MHD shear Alfvén wave may turn into unstable firehose instability by affecting the nature of the pure MHD waves. It is reported that the CGL fluid model describes the growth rate of firehose instability very accurately at sufficiently long spatial scales [25].…”
mentioning
confidence: 99%
“…Hunana et al [23] have presented a detailed review of CGL fluid description in collisionless plasmas and shown the importance of heatflux vectors in astrophysical plasmas. Wang and Hau [24] found that in a homogeneous anisotropic plasma, MHD shear Alfvén wave may turn into unstable firehose instability by affecting the nature of the pure MHD waves. It is reported that the CGL fluid model describes the growth rate of firehose instability very accurately at sufficiently long spatial scales [25].…”
mentioning
confidence: 99%